No rastro da memória: fotografia e pedagogia da imagem - Silva, Thalia Ferreira (2021)
This essay approaches the photography´s theme being delimited by the presence of technical images in pedagogical processes dialoguing with other space-times that contribute to the cultural formation of contemporary subjects. As an object of investigation and observation, we propose the construction of a photographic essay to guide our investigation on the following question: What are the aesthetic-epistemological characteristics that the photo essay makes possible for a pedagogical image? The research aims to: conceptualize photography and technical image from the thought of Vilém Flusser and Walter Benjamin by relating these authors' concepts with the pedagogy of image. The photo essay will be composed of approximately twenty-two images, built from the aesthetics of the avant-garde art movement Surrealism and presented as a pedagogical activity to undergraduate students as a way of exploring the relationship between image, experience and learning. Our theoretical framework is based on Walter Benjamin and Vilém Flusser´s philosophy, conceptualizing technical images, devices, aura and magic, mobilizing the concepts to think about the reproduction and reception of works based on their technical reproducibility. As a result of this investigation, we argue that even in the incessant technical reproduction, we see paths for a pedagogy of the image based on photography, once it has the potential to produce shocks and estrangements that may cause thought and aesthetic enjoyment, instead of a pure representation of objects from reality produced by devices who are capable to generate technical images.